Metabolomics-based discovery of XHP as a CYP3A4 inhibitor against pancreatic cancer - Yang, Yuting; Guo, Yanlei; Luo, Hua; Wang, Menglei; Chen, Fang; Cui, Huawei; Chen, Ping; Yin, Zhujun; Li, Li; Dai, Ying; Zeng, Jin; Zhao, Junning (Frontiers in Pharmacology, 2023)
The Background： Xihuang Wan (XHW), a purgative and detoxifying agent, is mainly used for the treatment and adjuvant treatment of various malignancies such as breast cancer, liver cancer and lung cancer, modernly. One clinical study found that XHW in combination with gemcitabine can be used to treat pancreatic cancer (PC). This suggests that XHW as a broad antitumour herbal combination may be used in the treatment of PC. However, the effect and mechanism of XHW in treating pancreatic cancer are unknown. Aim of the study: In this study, we explored the main active ingredients of XHP using a modified dosage form of XHW, Xihuang Pills (XHP). XHP alone was shown to have anti-PC effects by in vivo and in vitro pharmacodynamic methods, and potential key targets for XHP in the treatment of PC were identified using a Widely-targeted metabolomics approach. Materials and methods: The XHP component was quantified using UPLC/Q-TOF-MS. In vitro, we determined the role of XHP against SW1990 pancreatic cancer cells using CCK-8, Hoechst 33258 and flow cytometry. For in vivo experiments, we established a xenograft mouse model of PC. The anti-PC effect of XHP in vivo was examined by immunohistochemistry and Tunel apoptosis assay. Differential metabolites were screened by Widely-targeted metabolomics to find new targets of XHP for PC treatment and validated by Western Blot and RT-PCR. Results: We determined that XHP contained AKBA, KBA, 4-methylene-2,8,8-trimethyl-2-vinyl-bicyclo[5.2.0]nonane and (1S-endo)-2-methyl-3-methylene-2-(4-methyl-3–3-pentenyl)-bicyclo[2.2.1heptane. In vitro results showed that XHP inhibited the growth and promoted the apoptosis of SW1990 pancreatic cancer cells. In vivo results showed that oral administration of XHP significantly inhibited the growth of PC xenograft tumours in Balb/c mice and promoted apoptosis of cancer cells. In addition, we found that the Steroid hormone biosynthesis metabolic pathway plays a key role in the anti-PC effect of XHP in mice based on Widely-targeted metabolomics. CYP3A4 was screened as a potential therapeutic target by differential metabolites and validated by Western Blot, RT-PCR. Conclusion: Our study found that XHP has anti-PC effects. And using Widely-targeted metabolomics, CYP3A4 was found to be a key potential target of XHP for the treatment of PC.